2016
DOI: 10.3109/0284186x.2015.1118658
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of radiation-induced gastrointestinal morbidity: A prospective, longitudinal study following radiotherapy for carcinoma of the prostate

Abstract: Background Chronic gastrointestinal (GI) morbidity occurs in ≥50% of patients after external beam radiotherapy (EBRT) for carcinoma of prostate (CaP). This prospective, longitudinal study examines which baseline measurements of: 1) homocysteine and micronutrients in plasma; 2) chromosome damage/misrepair biomarkers; and 3) anal and rectal dose volume metrics predict GI morbidity after EBRT. Patients and methods In total, 106 patients with CaP had evaluations of GI symptoms (modified LENT-SOMA questionnaires) b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 26 publications
0
10
1
Order By: Relevance
“…The lesser impairment of pudendal nerve function in this study is reflected in the absence of evidence of atrophy of the anal sphincters on ultrasound although the internal and EASs were thinner in the patients !2 years after 3D-CRT ± HDR brachytherapy compared with age matched patients before radiotherapy. The differences in % of patients treated with 3D-CRT in this study (100%) compared with our previous study (18%) and in the median time since completion of radiotherapy (5 years for present versus 8 years for previous study) suggest that greater sparing by the universal application of 3D-CRT in this study and/or progressive damage to the pudendal nerves in the previous study [20] are likely explanations for the less severe pudendal nerve dysfunction reported here.…”
Section: Discussioncontrasting
confidence: 57%
See 3 more Smart Citations
“…The lesser impairment of pudendal nerve function in this study is reflected in the absence of evidence of atrophy of the anal sphincters on ultrasound although the internal and EASs were thinner in the patients !2 years after 3D-CRT ± HDR brachytherapy compared with age matched patients before radiotherapy. The differences in % of patients treated with 3D-CRT in this study (100%) compared with our previous study (18%) and in the median time since completion of radiotherapy (5 years for present versus 8 years for previous study) suggest that greater sparing by the universal application of 3D-CRT in this study and/or progressive damage to the pudendal nerves in the previous study [20] are likely explanations for the less severe pudendal nerve dysfunction reported here.…”
Section: Discussioncontrasting
confidence: 57%
“…The prevalence of unilateral and/or bilateral pudendal nerve injury in the current study was increased if a number of actual (rather than modeled in our previous study [11]) radiation dose volume parameters were exceeded including pudendal nerve, rectal and anal Dmax >60 Gy. Although these parameters have not been previously reported as dose constraints for radiotherapy treatment planning, Dmean anal and V 40 Gy anal have been associated respectively with an increased risk of FI and increased total GI symptom scores after radiotherapy for prostate carcinoma [20,22]. Differences in the definition of the anal canal (contoured separately from the rectum) and statistical analyses of the data between the studies were proposed to account for the finding of a volume [20] as opposed to a dose [22] constraint in the previous studies [20,22].…”
Section: Discussionmentioning
confidence: 89%
See 2 more Smart Citations
“…The technique is based on 3 observations: low dose hyper-radiosensitivity, evidence of a transition dose beyond which DNA damage repair is triggered, and the observation of improved DNA damage repair for normal tissue at low dose rates. [5][6][7][8][9][10] The theory is that tumor cells have a higher dose threshold to initiate DNA repair than normal tissues.…”
Section: Introductionmentioning
confidence: 99%